2016
DOI: 10.1111/cob.12165
|View full text |Cite
|
Sign up to set email alerts
|

Association between ratio indexes of body composition phenotypes and metabolic risk in Italian adults

Abstract: (2016) Association between ratio indexes of body composition phenotypes and metabolic risk in Italian adults. Clinical Obesity,6 (6 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Instead, the fat mass to fat-free mass ratio (F2FFMR) may be a superior indicator of the ability to maintain homoeostasis at the level of the organ or tissue. F2FFMR can be used for the prediction of metabolic risk in population-based studies [ 16 ]. However, it is not clear whether changes in F2FFMR have effects, and how fat mass and fat-free mass ratio changes.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the fat mass to fat-free mass ratio (F2FFMR) may be a superior indicator of the ability to maintain homoeostasis at the level of the organ or tissue. F2FFMR can be used for the prediction of metabolic risk in population-based studies [ 16 ]. However, it is not clear whether changes in F2FFMR have effects, and how fat mass and fat-free mass ratio changes.…”
Section: Introductionmentioning
confidence: 99%
“…Men showed a stronger association for education compared to other SEP measures, and also a stronger association than that observed in women when measured by education, whilst a heterogeneous association was observed for occupational social class [ 33 ]. Another paper found that those with higher education level were more likely to have a normal compared to high ratio of fat to LM, whilst employment was related to the ratio in a non-linear fashion [ 62 ]. In the third study no association was found between income and the ratios of central fat types in females [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, which similarly compared different adiposity indexes in the screening of MetS in the general population, showed a discriminatory power for FMI [32], WC [33] and WHtR [34]. The reason for these differences could be that only a few indexes were compared in each of the above studies, which, moreover, were cross-sectional.…”
Section: Discussionmentioning
confidence: 96%